Combination of high‐density cholesterol level, elastic score, and severity of exocrine pancreatic dysfunction may be useful for a predictive factor for patients with early chronic pancreatitis. Issue 4 (13th December 2022) - Agawa, Shuhei; Futagami, Seiji; Watanabe, Yoshiyuki; Habiro, Mayu; Kawawa, Rie; Yamawaki, Hiroshi; Tsushima, Rina; Kirita, Kumiko; Noda, Hiroto; Akimoto, Teppei; Ueki, Nobue; Iwakiri, Katsuhiko
Abstract: Background: This study aimed to clarify whether any risk factors including clinical characteristics, endosonographic features, and exocrine pancreatic dysfunction may be useful for a predictive factor for patients with early chronic pancreatitis. Methods: A total of 163 consecutive patients that presented with functional dyspepsia with pancreatic enzyme abnormalities (FD‐P) ( n  = 46), early chronic pancreatitis (ECP) ( n  = 47), and asymptomatic patients with pancreatic enzyme abnormalities (AP‐P) ( n  = 70) based on the Rome III classification and the Japan Pancreatic Association were included in this study. The enrolled patients were evaluated using endosonography (EUS) and EUS elastography. The levels of the five pancreatic enzymes were measured. Pancreatic exocrine function was analyzed using N‐benzoyl‐l‐tyrosyl‐p‐aminobenzoic acid (BT‐PABA). Results: There were no significant differences in clinical characteristics such as age, gender, body mass index, alcohol consumption, and smoking among patients with AP‐P, FD‐P, and ECP. The ratio of BT‐PABA test less than 35% in patients with ECP was significantly ( P  = 0.043) higher than in AP‐P patients. Elastic score was a useful tool to differentiate the FD‐P group from the ECP group. The high‐density cholesterol levels in patients with ECP were significantly lower than those in AP‐P. In addition, the combination of total and high‐density cholesterol levels, BT‐PABA test, and elastic score has a higher area under the curve value (0.708) of patients with ECP than in the other groups. Conclusions: The combination of high‐density cholesterol levels, elastic score, and severity of exocrine pancreatic dysfunction may be useful for a predictive factor for patients with ECP.